Short-term clinical outcome of early onset colorectal cancer and bone metastasis progression: Evaluation of zoledronic acid effectivity in controlling the skeletal related events - Bagus, Budhi Ida; Setyono, Hanis; Wibisono, Wibisono; Suwardi, Suwardi (Edelweiss Applied Science and Technology, 2025)
The incidence of early-onset colorectal cancer (EOCRC), which affects people under 50 worldwide, has increased by nearly 30% over the past 20 years, particularly in high-income nations. Fifty percent of patients will experience metastases following surgical treatment of the primary tumor, and 20% have metastatic disease at the time of diagnosis. The main factors associated with patient morbidity are skeletal-related events (SREs), which frequently manifest as spinal cord compression, bone pain, pathological fractures, and hypercalcemia. This study aims to evaluate the short-term clinical outcomes of pharmacologic treatment options for bone metastasis related to early-onset colorectal cancer undergoing definitive surgical resection and adjuvant chemotherapy, which progresses to skeletal-related events. The study will include both resectable colorectal adenocarcinomas. Patients with a prior history of neoadjuvant chemotherapy will be excluded. The primary clinical outcome to be assessed is pain reduction associated with bone metastasis after zoledronic acid treatment over six months. From January 2023 to January 2025, we reported 15 cases of early-onset colorectal cancer that progressed to bone metastasis after resection and adjuvant treatment. Seven cases involved sigmoid adenocarcinoma. The most common symptom was chronic pain. Pain levels, measured by the Visual Analog Scale (VAS), improved after six cycles of zoledronic acid treatment, with no further reports of worsening skeletal-related events. Early diagnosis of colorectal cancer is crucial, as early-onset cases have a higher likelihood of spreading to the bones. Pharmacologic therapy demonstrates a favorable clinical outcome in controlling symptoms related to skeletal-related events.